PELATIHAN & PENYULUHAN PEMBUATAN IPAL INDUSTRI TAHU DENGAN MENGGUNAKAN METODE FITOREMEDIASI SEBAGAI PENETRAL LIMBAH DENGAN MENGGUNAKAN ECENG GONDOK DI DESA SUKA MAKMUR KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Darlina Tanjung; Marwan Lubis; M. Husni Malik Hasibuan; Jupriah Sarifah; Ronal HT. Simbolon (Cattleya Darmaya Fortuna, 2024)
This community service aims to improve the management of tofu industry liquid waste in Suka Makmur Village, Deli Tua District, Deli Serdang Regency, through training and counseling on the construction of a Wastewater Treatment Plant (WWTP) based on phytoremediation with water hyacinth. The tofu industry in this area produces liquid waste with a capacity of 2,000 L/day, which contains high organic pollution with BOD 50.5 mg/L, COD 130 mg/L, TSS 135 mg/L, and pH 5. Through the implementation of phytoremediation, after processing in an equalization tank, sedimentation, and phytoremediation, the quality of the waste increased significantly with BOD decreasing to 20.5 mg/L, COD to 39.5 mg/L, TSS to 22.5 mg/L, and pH to 6. These results indicate that the quality of the effluent has met the quality standards according to Permen LHK No. 68 of 2016. This activity not only helps overcome waste pollution but also provides practical training for UMKM actors in the area.